Aktivitas Antibakteri Ekstrak Etanol Daun Harendong Bulu (Clidemia Hirta) asal Maluku terhadap Staphylococcus Aureus - Aulia Debby Pelu; Jayanti Djarami (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2022)
Pleroma urvilleanum (Clidemia hirta) is a plant that is widely found in Maluku, which contains chemical compounds, including tannins (catechols and pyrogalotanins), dioxyanthraquinones, steroids, saponins, glycosides and phenols which of these contents can function as antibacterial. This study aimed to determine the antibacterial activity of the ethanol extract of Pleroma urvilleanum(Clidemia hirta) leaf from Maluku with various concentrations of 5%, 25%, 50% and 75% against the growth of Staphylococcus aureus bacteria. The research design used is an experimental laboratory using the agar diffusion method by means of wells. The results of the study showed that at a concentration of 5%, it has an inhibitory power of 20 mm with a strong category. While at a concentration of 25% it has an inhibitory power of 29 mm, at a concentration of 50% it has an inhibitory power of 34 mm and at a concentration of 75% has an inhibitory power of 35 mm with a very strong category. Conclusion: ethanol extract Pleroma urvilleanum (Clidemia hirta) leaf from Maluku has antibacterial activity against the growth of Staphylococcus aureus bacteria and the higher the concentration, the greater the antibacterial activity.Keywords: Antibacterial activity, Harendong bulu (Clidemia hirta), Staphylococcus aureus, Moluccas